Aspects of the ecology of leopards (Panthera Pardus) in the Little Karoo, South Africa - Mann, Gareth (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
Leopards (Panthera pardus) are the most common large predators, free roaming outside of protected areas across most of South Africa. Leopard persistence is attributed to their tolerance of rugged terrain that is subject to less development pressure, as well as their cryptic behaviour. Nevertheless, existing leopard populations are threatened indirectly by ongoing transformation of natural habitat and directly through hunting and conflict with livestock farmers. Together these threats may further isolate leopards to fragmented areas of core natural habitat. I studied leopard habitat preferences, population density, diet and the attitudes of landowners towards leopards in the Little Karoo, Western Cape, South Africa, an area of mixed land-use that contains elements of three overlapping global biodiversity hotspots. Data were gathered between 2010 and 2012 using camera traps set up at 141 sites over an area of ~3100kmÂ², GPS tracking collars fitted to three male leopards, scat samples (n=76), interviews with landowners (n=53) analysed in combination with geographical information system (GIS) layers. My results reveal that leopards preferred rugged, mountainous terrain of intermediate elevation, avoiding low-lying, open areas where human disturbance was generally greater. Despite relatively un-fragmented habitat within my study area, the leopard population density (0.75 leopards/100kmÂ²) was one of the lowest yet recorded in South Africa. This may reflect low prey densities in mountain refuges in addition to historical human persecution in the area. Currently local landowners are more tolerant of leopards than other wildlife species with incidents of conflict involving leopards being rare relative to black-backed jackals (Canis mesomelas), baboons (Papio hamadryas), caracals (Caracal caracal) and porcupine (Hystrix africaeaustralis). Although current levels of conflict between leopards and stock farmers are low, leopards do depredate livestock, which constitute 10-15% of their diet. Improved livestock husbandry measures and co-operation between conservation authorities and farmers are necessary to mitigate such conflict and balance economic security with biodiversity conservation in the region. Leopards are the only remaining top predators throughout much of the Little Karoo and the Western Cape and as such are predicted to play a critical role in ecosystem structure and the survival of other species. Current high levels of connectivity between areas of suitable leopard habitat bode well for the conservation status of leopards within this region and future conservation efforts need to ensure that narrow corridors linking such habitat are preserved. The potential for leopards to serve as both an umbrella and a flagship species for biodiversity conservation suggests that long term monitoring of this population would be a conservation priority for the Little Karoo.
Keywords: Leopard -- South Africa -- Little Karoo; Leopard -- Monitoring -- South Africa -- Little Karoo; Leopard -- Ecology -- South Africa -- Little Karoo; Wildlife monitoring -- South Africa; Wildlife conservation -- South Africa; Animal populations -- South Africa -- Little Karoo; Leopard -- Conservation -- South Africa -- Little Karoo